1999
DOI: 10.1007/s002210050670
|View full text |Cite
|
Sign up to set email alerts
|

Feedforward versus feedback control in children and adults subjected to a postural disturbance

Abstract: Any action performed by standing subjects is generally accompanied by compensatory postural activities, which reduce or abolish the postural disturbance generated by the movements and keep the subjects' center of gravity within the supporting base. These postural activities are triggered by either anticipatory and/or feedback-based control processes, depending on the information available and on the behavioral context. To investigate the respective involvement of these two components in postural control during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 26 publications
6
31
0
2
Order By: Relevance
“…Two factors may explain this observation: The younger children had a less stable initial posture and/or a lack in cognitive control of the movement. Our results confirmed previous findings indicating that (1) the expression of anticipatory postural adjustments was still developing during mid-childhood and (2) the adult-like pattern was not reached at 8 (Hay and Redon, 1999;McFadyen et al, 2001;Schmitz et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Two factors may explain this observation: The younger children had a less stable initial posture and/or a lack in cognitive control of the movement. Our results confirmed previous findings indicating that (1) the expression of anticipatory postural adjustments was still developing during mid-childhood and (2) the adult-like pattern was not reached at 8 (Hay and Redon, 1999;McFadyen et al, 2001;Schmitz et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…According to these authors, the feedforward control is fully developed approximately at 7 years old. Hay and Redon (1999) showed that the contribution of the feedforward processes to postural control evolve non-monotonically between 3 and 10 years old. Although postural responses of 6-year-old children were almost similar to those of adults, the feedforward control appeared to be less efficient for the 9-to 10-year-old children.…”
Section: Introductionmentioning
confidence: 99%
“…Similar patterns of motor task prioritization have been observed in older adults (Li et al, 2001;Rapp et al, 2006). Our results also match findings demonstrating developmental phases of temporary overcontrol of posture during childhood (Hay & Redon, 1999;Kirshenbaum, Riach, & Starkes, 2001). Young adults, on the other hand, who showed less body sway than children when balancing on the board, can "afford" to increase their sway under dual-task conditions without risking their balance.…”
Section: Discussionsupporting
confidence: 90%
“…A potential explanation is that the kinds of resources required to perform the two tasks concurrently originate from different and distinguishable resource pools (Navon & Gopher, 1979) instead of a unique, general-purpose unit or structure (Kahneman, 1973). In this vein, the distinction between feedforward and feedback control of balance proposed by Hay and Redon (1999) could elucidate the processes required when balancing on the stable or moving platform. According to that account, feedforward control comes into play when an individual's own movements generate balance disturbances, and "anticipatory" postural adjustments can be triggered prior to the self-induced disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…However, disturbed body balance does not necessarily reflect functioning of the balancing system, but may be also associated with growth-related changes, side effects of taken medicines, or disorders of spatial orientation (Cho and Kamen, 1998;Waśkiewicz, 2002;Kostiukow et al, 2009). According to literature, stabilization of body posture in children being under intensive biological development should be reflected by a decrease in the number body sways and degree of COP displacement (Hay and Redon, 1999).…”
Section: Discussionmentioning
confidence: 99%